PENGARUH SAYUR BENING DAUN KELOR (MORINGA OLEIFERA) PADA IBU HAMIL DI PUSKESMAS PATUMBAK DELISERDANG TAHUN 2022 - Chandra Juita Pasaribu; Adriana Bangun; Eka Ristin Tarigan (BEST Journal (Biology Education, Sains and Technology), 2023)
Anemia is a condition of the body in which the level of hemoglobin (Hb) in the blood is lower than normal (WHO, 2011). Pregnant women are prone to anemia because they need more nutrients than usual to meet their own needs and for the growth and development of the fetus. Pregnant women are declared anemic if their hemoglobin level is less than 11 mg/L. This study used an analytic research design using a quasy experimental approach in the form of a pretest and posttest control group design. The purpose of this study was to determine the effect of giving Moringa oleifera clear vegetable leaves (Moringa oleifera) on hemoglobin levels in pregnant women at the Patumbak Health Center in 2022. The sample size in this study used a total sampling technique, namely 30 pregnant women in the Patumbak Health Center Medan work area. The data used in this study were primary data obtained by interview using a questionnaire sheet which was given directly to the respondent and checking/measuring Hb levels during the study. The results showed that the average hemoglobin level of the respondents during the pre-test, the average hemoglobin level of the respondents during the post-test was 18.8 and there was an effect of giving Moringa oliefera leaf extract on the hemoglobin level of pregnant women. It is hoped that pregnant women will diligently consume Moringa leaves to be used as supplements and vegetables which are relatively cheap, easy and safe to use to treat iron deficiency anemia, so that health workers provide counseling to the public, especially pregnant women, about the potential of Moringa leaves as vegetables that have high nutritional value and consumption of the leaves. Moringa can be used as an alternative source of iron to overcome cases of malnutrition, including iron nutritional anemia. It is necessary to make a food formula from moringa leaf powder that can be consumed by the public, so that it can be used to prevent anemia due to iron deficiency.